Advances and challenges of life cycle assessment (LCA) of greenhouse gas removal technologies to fight climate changes. (20th January 2020) - Goglio, P.; Williams, A.G.; Balta-Ozkan, N.; Harris, N.R.P.; Williamson, P.; Huisingh, D.; Zhang, Z.; Tavoni, M.
Abstract: Several greenhouse gas removal technologies (GGRTs), also called negative emissions technologies (NET) have been proposed to help meet the Paris Climate Agreement targets. However, there are many uncertainties in the estimation of their effective greenhouse gas (GHG) removal potentials, caused by their different levels of technological development. Life Cycle Assessment (LCA) has been proposed as one effective methodology to holistically assess the potential of different GGRT removal approaches but no common framework is currently available for benchmarking and policy development. In this article, challenges for LCA are reviewed and discussed together with some alternative approaches for assessment of GGRTs. In particular, GGRTs pose challenges with regards to the functional unit, the system boundary of the LCA assessment, and the timing of emissions. The need to account within LCA of GGRTs for broader implications which involve environmental impacts, economic, social and political drivers is highlighted. A set of recommendations for LCA of GGRTs are proposed for a better assessment of the GGRTs and better accounting of their carbon removal potentials to meet the targets established within the Paris Agreement. Highlights: LCA functional units of greenhouse gas removal technologies (GGRTs) were proposed. System boundaries are a GGRT challenge as they involve different production systems. Emission time is key in the LCA of GGRT as removals do not happen at the same time. LCA of GGRTs should address environmental, economic, social, political implications. Recommendations to improve LCAs of GGRTs were proposed.